Reading gender by the column inch analyzing gender representation in Philippine print advertisements - Rapanot, Czekaina Esrah; Paragas, Fernando de la Cruz; Mangalus, Marrhon; Hoggang, Catherine Faith; Agonos, Mariam Jayne (2021)
Access online through this link: https://www.plarideljournal.org/article/reading-gender-by-the-column-inch-analyzing-gender-representation-in-philippine-print-advertisements
Keywords: Print advertising; Gender stereotypes; Digital media